INTER-CULTURAL TRANSLATION AS INTERPRETATION AND COMMUNICATION - Rudaitytė, REGINA (Vertimo studijos, 2017)
The paper focuses on literary translation regarded as a creative process and a powerful culture-shaping activity. It also looks at the complexities of inter-cultural translation: problems occurring in translating from one cultural system into another, and the possible strategies to be adopted; as well as some intricate issues of a more general and conceptual character, such as the limits of translatability, the divide, if any, between good and bad translation, the possible approaches to dealing with culture-specific items in translation, retaining the concept of ‘otherness’, of foreignness. The issue of foreignness also raises the question of the role of translation in the globalized world. Hence what are the effects of English, as the global lingua franca, and cultural imports from great powers, like the USA, UK and France on the cultures and languages of small countries? Apart from releasing ‘the shaping power of one culture upon another’, translation can also be detrimental to their national identity by encroaching on their cultures.